MORBIDITY PROFILE OF ELDERLY POPULATION IN AN URBAN FIELD PRACTICE AREA - Dr. Ritesh P. Kundap, Dr. Saptarishi Bose (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: With advancing age, Indian urban populations are increasingly challenged by acomplex burden of chronic diseases and functional decline. Understanding morbidity patternsis essential for planning geriatric health services.